Age‐related progression of Alzheimer disease neuropathologic change (ADNC) in cognitively normal individuals: Toward a definition of resilience and resistance. (December 2021) - Walker, Jamie M.; Dehkordi, Shiva Kazempour; Richardson, Timothy E.; Zare, Habil
Abstract: Background: An intriguing group of individuals, termed "resilient", demonstrate neuropathologic changes consistent with Alzheimer disease (AD), yet display no cognitive impairment. Neuropathologic studies have reported less neuronal loss overall, less gliosis, and fewer comorbidities in these individuals. We sought to investigate the unique clinical characteristics of this subgroup as well as individuals who are "resistant" to AD neuropathologic change. Method: Utilizing data from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS) and Neuropathology Data Set, we demonstrate the age‐related progression of AD neuropathologic changes in all individuals (cognitively impaired and normal, n=6, 144) as well as in only cognitively normal individuals (CDR = 0, n=662). With plots generated from these data, we have established standard lines that may be used to measure the extent to which an individual's AD pathology varies from the estimated normal range of pathology. We have also defined levels of AD neuropathologic change above which an individual could be considered "resilient" against the neuropathologic changes and levels below which an individual could be considered "resistant" to the neuropathologic changes. With this definition, we have identified 43 resilient and 23 resistant individuals and have analyzed the UDS for any significant clinical variations in these subgroups of individuals. Result: Our plots demonstrate that although Braak stage and Thal phase increase with age in cognitively normal individuals, CERAD neuritic plaque score and ADNC remain at low levels, suggesting a critical role for neuritic plaques in the development of cognitive decline. Analyses of NACC UDS and NP datasets comparing resilient to other CDR = 0 individuals revealed significant differences in medication use, as well as comorbid pathologies. When comparing resistant individuals to other cognitively normal individuals, we found variations in blood pressure, as well as neuropsychiatric differences and subjective differences in the clinical impression of an individual's cognition without CDR scores indicating MCI. Conclusion: In conclusion, we are able to identify resilient and resistant individuals based off of a linear model of Braak stage progression with age. These individuals display differences that could provide insight into the protective mechanisms by which they evade the neuropathologic changes and/or associated cognitive decline observed in AD.